2007
DOI: 10.1159/000099326
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Prior Treatment with Fluoride on Genotoxicity of Two Chemical Agents in vitro

Abstract: The goal of this study was to investigate the ability of fluoride to modulate the genotoxic effects induced by the oxidative agent hydrogen peroxide (H2O2) and the alkylating agent methyl methanesulfonate (MMS) in vitro by the single-cell gel (comet) assay. Chinese hamster ovary cells were exposed in culture for 1 h at 37°C to sodium fluoride at 7–100 µg/ml. NaF-treated and control cells were then incubated with 0–10 µM MMS in phosphate-buffered saline (PBS) for 15 min at 37°C, or 0–100 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Cepacol® and Plax® contain high concentration of sodium fluoride. Previous studies conducted by our group have demonstrated that sodium fluoride did not cause genetic damage either in vitro or in vivo [29,30]. Regardless of the biological phenomenon involved in this process, we assumed that Periogard® is a mutagenic agent as a result of chromosomal breakage or loss in buccal mucosa cells.…”
Section: Discussionmentioning
confidence: 91%
“…Cepacol® and Plax® contain high concentration of sodium fluoride. Previous studies conducted by our group have demonstrated that sodium fluoride did not cause genetic damage either in vitro or in vivo [29,30]. Regardless of the biological phenomenon involved in this process, we assumed that Periogard® is a mutagenic agent as a result of chromosomal breakage or loss in buccal mucosa cells.…”
Section: Discussionmentioning
confidence: 91%
“…Earlier reports regarding the genotoxic potential of F during in vitro (Anuradha et al, 2001;Ha et al, 2004;Liu et al, 2007;Machalinska et al, 2001) and in vivo (He and Chen, 2006) studies in humans (Gadhia and Joseph, 1997) and rodents (Podder et al, 2008(Podder et al, , 2011 are conflicting. Some studies demonstrated that F did not produce damage to the genetic material (Li et al, 1987;Ribeiro et al, 2006;Ribeiro et al, 2007;Skare et al, 1986). Other studies on oxidative stress in fluorotic humans and F-intoxicated animals indicated that generation of reactive oxygen species (ROS) and lipid peroxidation may be directly induced by F (Ailani et al, 2009;Inkielewicz et al, 2006;Podder et al, 2008;Susheela and Bhatnagar 2002).…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
“…However, it is well known that X-rays can induce cytotoxic effects and cause DNA damage. 2,3 Considering the strong evidence for a relationship between genetic damage/cytotoxicity and carcinogenesis, 4 an investigation of the noxious effects induced by dental X-rays is necessary to identify the degree of risk involved and minimize potential risks to patients and clinicians. The purpose of this article is to provide a review of the biomonitoring data of dental X-ray in oral mucosa cells, based on our recent research within the field.…”
Section: Introductionmentioning
confidence: 99%